An Association between External Hydrocephalus in Infants and Reversible Collapse of the Venous Sinuses - Bateman, Grant A.; Alber, Michael; Schuhmann, Martin U. (Neuropediatrics, 2014)
The etiology of external hydrocephalus is usually ascribed to either a delay in maturation or obstruction of the arachnoid granulations, but the arachnoid granulations are absent in neonates. Venous outflow stenoses, similar to those seen in idiopathic intracranial hypertension (IIH), have been described in external hydrocephalus. A reversible collapse of the sinuses is known to operate in IIH, but collapsible sinuses have not been previously described in infants with external hydrocephalus. Three infants with external hydrocephalus had magnetic resonance venography at differing time points during their illness. The venous sinuses varied in size depending on the cerebrospinal fluid pressure similar to IIH in adults. External hydrocephalus may be analogous to IIH in adults.
Keywords: external hydrocephalus; MR venography; venous sinus; stenosis; idiopathic intracranial hypertension